“Crime and punishment”: the ethical fundaments in the control regime of common fisheries policy - Coelho, Manuel (2013)
Monitoring and enforcement in fisheries have been largely neglected in the study of management in this field. A formal model of fisheries law enforcement is presented to show how fishing companies perform their activities and how fisheries policies are affected by costly, imperfect enforcement of fisheries law. The model developed combines standard Economics of Fisheries analysis (Gordon/Schaefer model) and the Theory of “Crime and Punishment” of Becker. The Common Fisheries Policy (CFP) is discussed. And in the model presented is considered its possible use.